Stimulating Students’ Critical Mathematical Thinking through STEAM-Based Mitigation Learning Activities: Design and Validation - Pramasdyahsari, Agnita Siska; Setyawati, Putri; Setyawati, Rina Dwi; Dahal, Niroj (Pendidikan Matematika UNIMOR, 2025)
Integrating Science, Technology, Engineering, Art, and Mathematics (STEAM) with real-world issues, such as disaster mitigation in mathematics education, has the potential to foster students’ critical thinking through interdisciplinary and problem-based learning. However, existing instructional designs often lack contextual relevance and do not fully incorporate STEAM principles or the Engineering Design Process (EDP). This study employed a research and development approach using the 4D model (Define, Design, Develop, Disseminate) to create STEAM-based mathematics learning activities centred on disaster mitigation topics. Ten ninth-grade mathematics teachers from junior high schools in Semarang and Blora were involved in the development and validation process. Data were collected through expert validation sheets and teacher questionnaires, and analyzed using the Rasch model with the Winstep application. The developed learning activities demonstrated high reliability with a Rasch reliability coefficient of 0.90, indicating strong internal consistency and practical relevance. Expert validation confirmed the content and construct validity of the materials, supporting their feasibility for classroom implementation. The validation results suggest that the design is potentially suitable for classroom implementation, based on expert judgment and instrument validation outcomes. The study provides a validated and practical design for STEAM-based mathematics instruction that contextualizes disaster mitigation to enhance students’ critical thinking. Moreover, this innovative integration of STEAM and EDP offers a validated, practical STEAM-based mathematics learning design that supports teachers and enhances students’ critical thinking through real-world contexts. Its novelty is that it integrates STEAM and the EDP into disaster-themed mathematics learning to contextualize problem-solving and enhance students’ critical thinking.